Saccharomyces cerevisiae linhagem UFMG A-905 enriquecida com selênio diminui inflamação no jejuno causada por mucosite induzida por 5-fluorouracil - Bárbara Abranches de Araújo Pôrto (2016)
Gastrointestinal mucositis is the major problem associated with cancer therapy (chemotherapy and radiotherapy). However, there is no effective therapy against this side effect. The anti-metabolite 5-fluorouracil (5-FU) agent is used in cancer treatment, but this drug causes gastrointestinal damage, especially on mucous membranes, leading to changes in intestinal permeability, bacterial translocation and immunity. Inflammation is the first response against infectious agents and tissue ischemia. Among the inflammatory processes of mucositis, formation of reactive oxygen species (ROS) plays a very important role in its development. To minimize the deleterious effects of ROS there are some antioxidant defenses, which selenium (Se) presents an important function because it is a component of selenoproteins, having antioxidant functions, and this metal is necessary for cellular detoxification. Currently there is a growing interest in the use of yeasts enriched with Se because they are able to convert inorganic Se into selenomethionine, which can be better metabolized by mammals. The use of yeasts for human and animal consumption is already being done through probiotics. The yeast Saccharomyces cerevisiae strain UFMG-905 was selected and studied by our group for its probiotic potential. In animal models with mucositis induced by irinotecan (chemotherapeutic drug), this yeast was able to decrease oxidative stress, preserving goblet cells and recovering the intestinal mucous membrane when used as a probiotic. Therefore, treatment with the yeast enriched with Se can be a good alternative in minimizing the side effects of the drug 5-FU in patients undergoing cancer treatment. Thus, our two main objectives were: (i) evaluate the incorporation of Se by yeast using a proteomic approach, and (ii) verify its potential for use as a probiotic supplemented with Se in an animal model of mucositis induced by 5-FU . When this yeast was used to treat mucositis, our results demonstrated that treatment with yeast and yeast enriched with Se, were able to reduce intestinal permeability and improved histology. Treatment with yeast enriched with Se attenuated the inflammatory parameters therefore decreased lipid peroxidation, concentration of nitrites, resulting in a decrease recruitment of eosinophils, neutrophils and chemokine CXCL1 / KC in the jejunum, thus demonstrating the probiotic and antioxidant potential of such yeast when associated with organic Se.